TRNA methylation: An unexpected link to bacterial resistance and persistence to antibiotics and beyond. (13th June 2020) - Hou, Ya‐Ming; Masuda, Isao; Foster, Leonard J.
Abstract: A major threat to public health is the resistance and persistence of Gram‐negative bacteria to multiple drugs during antibiotic treatment. The resistance is due to the ability of these bacteria to block antibiotics from permeating into and accumulating inside the cell, while the persistence is due to the ability of these bacteria to enter into a nonreplicating state that shuts down major metabolic pathways but remains active in drug efflux. Resistance and persistence are permitted by the unique cell envelope structure of Gram‐negative bacteria, which consists of both an outer and an inner membrane (OM and IM, respectively) that lay above and below the cell wall. Unexpectedly, recent work reveals that m 1 G37 methylation of tRNA, at the N 1 of guanosine at position 37 on the 3′‐side of the tRNA anticodon, controls biosynthesis of both membranes and determines the integrity of cell envelope structure, thus providing a novel link to the development of bacterial resistance and persistence to antibiotics. The impact of m 1 G37‐tRNA methylation on Gram‐negative bacteria can reach further, by determining the ability of these bacteria to exit from the persistence state when the antibiotic treatment is removed. These conceptual advances raise the possibility that successful targeting of m 1 G37‐tRNA methylation can provide new approaches for treating acute and chronic infections caused by Gram‐negative bacteria. This article is categorized under: Translation > Translation Regulation RNA Processing > RNA Editing and Modification RNA Structure and Dynamics > Influence of RNA Structure in Biological Systems Abstract : Gram‐negative bacteria such as Escherichia coli and Salmonella use the TrmD‐catalyzed m 1 G37 methylation of tRNA to translate genes for the cell envelope double‐membrane structure. Active cell envelope confers multidrug resistance and persistence to these bacteria, permitting regrowth upon removal of antibiotics, whereas defective cell envelope sensitizes them to antibiotic killing.